Increasing Returns in General Non-Competitive Analysis - Silvestre, Joaquim (Econometrica, 1978)
[Arrow and Hahn's book General Competitive Analysis offers (Section 6.4) an existence theorem for non-competitive general equilibrium. Their formulation is apparently very general, but it becomes seriously restrictive in the presence of increasing returns to scale. An alternative existence theorem is presented here that obviates these shortcomings.]